2017
DOI: 10.1038/srep39911
|View full text |Cite
|
Sign up to set email alerts
|

Microbial taxa and functional genes shift in degraded soil with bacterial wilt

Abstract: Soil degradation is a serious global problem, but little is known about how soil microbial communities respond to soil degradation as well as their feedback to ecosystem functioning. In this study, we found the microbial community composition, structure and functional potential significantly altered in the degraded soils with bacterial wilt (termed as degraded soils). Compared with healthy soils, OTU richness of beneficial microorganisms were significantly decreased, but OTU richness of pathogenic microorganis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
55
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 64 publications
(62 citation statements)
references
References 43 publications
6
55
1
Order By: Relevance
“…The soil fungal community of lotus ( Nelumbo nucifera ) in healthy and Fusarium wilt‐infected fields showed significant differences, indicating reduction of beneficial microorganism and accumulation of fungal pathogens under continuous lotus cultivation (Cui, Wang, Zeng, & Sun, ). These results are in line with the above cited observations on microbial dysbiosis in pea (Xu et al, ; Yu et al, ), peanut (Li et al, ), and tobacco (Zhang et al, ). Such an approach will allow to select plant genotypes that associate with a disease‐suppressive or “healthy” microbiome that can restrict the virulence of predominant pathogens.…”
Section: Integrating the Microbiome To Improve Resistance Against Biosupporting
confidence: 92%
See 1 more Smart Citation
“…The soil fungal community of lotus ( Nelumbo nucifera ) in healthy and Fusarium wilt‐infected fields showed significant differences, indicating reduction of beneficial microorganism and accumulation of fungal pathogens under continuous lotus cultivation (Cui, Wang, Zeng, & Sun, ). These results are in line with the above cited observations on microbial dysbiosis in pea (Xu et al, ; Yu et al, ), peanut (Li et al, ), and tobacco (Zhang et al, ). Such an approach will allow to select plant genotypes that associate with a disease‐suppressive or “healthy” microbiome that can restrict the virulence of predominant pathogens.…”
Section: Integrating the Microbiome To Improve Resistance Against Biosupporting
confidence: 92%
“…Similar observations were made for long‐term peanut monocultures, where plant pathogenic fungi accumulated in the soil at the expense of beneficial fungi (Li et al, ). Zhang et al () took microbiome analysis a step further in their study on the sick soil phenomenon in monocropped tobacco fields. Combining amplicon sequencing with a functional gene analysis, the authors showed a shift in the microbial community composition to be accompanied by changes in the metabolic potential of genes involved in stress, virulence, and plant cell wall degradation in the sick soil.…”
Section: Complex Interactions Between Grain Legumes and Their Root‐asmentioning
confidence: 99%
“…Land degradation reduces soil microbial biomass and microbial activity [11], with reports of significant decrease in beneficial microorganisms and increase in pathogenic ones in degraded soils [12]. Another study [13] found higher bacterial richness and diversity in restored soils and soils under native vegetation in comparison to degraded soils.…”
Section: Land Degradation Neutrality (Ldn) Program Adopted By the Unimentioning
confidence: 95%
“…For example, Addy et al () reported a filamentous phage (φRSM) of the wilt‐causing bacterial pathogen Ralstonia solanacearum : φRSM infection made the pathogen less virulent and thus prevented damage to its host plants (Yamada, ). Ecologists have also been interested in φRSM because R. solanacearum is a serious threat to phytorestoration programs (Zhang et al, ), for example to programs to grow tobacco for ecorestoration of nutrient‐deficient and contaminant‐rich soils. In fact, degraded soils show greater abundance of not only R. solanacearum but also of pathogenic members of Pseudomonas , Erwinia , and Xanthomonas .…”
Section: Role Of Filamentous Phages In the Monitoring Bacterial Inocumentioning
confidence: 99%
“…Also, silverized antimicrobial phage fibers developed with E3 modified M13 kill bacterial contaminants in water during filtration through phage-coated fibers (Mao et al, 2010; (Yamada, 2013). Ecologists have also been interested in φRSM because R. solanacearum is a serious threat to phytorestoration programs (Zhang et al, 2017), for example to programs to grow tobacco for ecorestoration of nutrient-deficient and contaminant-rich soils.…”
Section: Phages For Biological Controlmentioning
confidence: 99%